Selectivity tuning options in hydrogenation of m-chloronitrobenzene to m-chloroaniline over mono- and bimetallic supported Pt catalysts - Mane, Rasika B.; Potdar, Aparna S.; Nadgeri, Jayprakash M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
Supported monometallic (Pt, Ni,) and bimetallic (Ni-Pt) catalysts were prepared for the selective liquid phase hydrogenation of m-chlronitrobenzene to m-chloroaniline (m-CAN). It was found that the use of sodium carbonate as an additive substantially reduced the extent of dehydrohalogenation in the case of monometallic, 1% Pt/C catalyst, to give the highest selectivity of 96% to m-CAN. Ni-Pt bimetallic catalyst although showed almost complete selectivity (>99%) to m-chloroaniline; its activity was several fold lower than that of 1% Pt/C Na2CO3 system. However, compared with Ni monometallic catalyst, bimetallic Ni-Pt showed higher activity and selectivity due to the presence of electron rich surface metallic Pt stabilized by Ni having lower ionization potential compared with Pt.